Accessibility to E-Commerce Websites for People with Disability in Indonesia - Hanny Hafiar; Syauqy Lukman; Yanti Setianti; Priyo Subekti; Kholidil Amin (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2023)
Using a website has become a primary method for delivering information, doing promotion, and marketing activities. E-commerce business people acknowledged the importance of developing a reliable website to reach the market through the internet, as part of e-service, especially in a country with a large market share like Indonesia. Unfortunately, not every e-commerce web designer is aware of the website accessibility criteria, the lack of awareness creates barriers for persons with disabilities to access e-commerce websites, as buyers and sellers. The accessibility gap of those website limits the ability of persons with disabilities to optimize the presence of e-commerce as an economic opportunity. We need to overcome the barriers to create an inclusive society in Indonesia. This paper aims to provide an overview of the accessibility of e-commerce websites in Indonesia, to find the common web accessibility issues, classified them comparatively into several tiers, type of issues, and then calculates the correlation of total issues with the number of visitors. This study analyzes 39 e-commerce websites. We evaluate based on Web Content Accessibility Guidelines (WCAG) 2.0, using an automated tool called